1983
DOI: 10.1139/v83-443
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of chiral hindered amides

Abstract: The static and dynamic structures of the amide derivatives of racemic and (R)-(+)-2-methoxy-2-phenyl-3,3,3-trifluoropropanoic acid (MPTA) with diisopropyl amine (1), meso-2,6-dimethylpiperidine (2), (R)-(−)- and (S)-(+)-2-methylpiperidine (3 and 4, respectively) were investigated by proton nmr spectroscopy. The piperidine rings adopt a single dominant conformation in which the substituent methyl groups occupy axial positions. One of the isopropyl groups of 1 is oriented in the same way as the corresponding sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 17 publications
(26 reference statements)
4
19
0
Order By: Relevance
“…The diastereoisomeric resolution of 2-methylpiperidine was accomplished by using commercially available (R)-(-)-mandelic acid as described by Craig and Pinder (1971) and Rauk et al (1983). This procedure was supposedly improved by Adamo et al (1999), but in our hands it failed to reproduce the reported yield.…”
Section: Resultsmentioning
confidence: 96%
“…The diastereoisomeric resolution of 2-methylpiperidine was accomplished by using commercially available (R)-(-)-mandelic acid as described by Craig and Pinder (1971) and Rauk et al (1983). This procedure was supposedly improved by Adamo et al (1999), but in our hands it failed to reproduce the reported yield.…”
Section: Resultsmentioning
confidence: 96%
“…To highlight the usefulness of the NMR method, only δ values of specific hydrogen atoms attached to sp 3 carbons are commented briefly (however, complete data is given in the Experimental section). In the 1 H-NMR spectrum of 8, the diastereotopic hydrogens attached to C2 (H2) constitute the AB part of an ABC system.…”
Section: Structure and Chemical Shift Correlationsmentioning
confidence: 99%
“…The detection of the low energy conformation 1 of the resulting amides is fundamental to establish the correlation between the chemical shifts (δ) of the hydrogen nuclei of the amine moiety and the configuration of the chiral derivatizing agent [2]. Although this strategy can be used to study the configuration of cyclic secondary amines, inherent ring conformations and slow rotation about amide bonds (see 2) make it difficult to interpret the NMR spectra [3]. In this context, incorporation of a 1-arylethyl group as the amidic nitrogen substituent, might be the recommended strategy to avoid free rotation about amide bond.…”
Section: Introductionmentioning
confidence: 99%
“…1 -3 After initial studies on the applications of Mosher's method to secondary amines by Tavares and coworkers, 4,5 Hoye and Renner summarized the common characteristics of 1 H NMR spectra of Mosher's amides derived from cyclic secondary amines with a chiral center in the ring. 6,7 It has been proved that Hoye's protocol can be an efficient guideline for assigning the absolute configuration or enantiomeric excess of substituted cyclic secondary amines.…”
Section: Introductionmentioning
confidence: 99%